PENGEMBANGAN MODEL KURIKULUM PENDIDIKAN BAHASA INGGRIS BERBASIS KKNI - Imroatus Solikhah (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2016)
The objective of this study is to promote model English language education curriculum in reference to Indonesian Qualifiation Framework (IQF), practically KKNI-Based English Curriculum. Curriculum evaluation implementing content analysis was used and qualitative approach that involved document analyses, interview, discussion, and workshop was utilized for data collection. This study discovers that alignment of terms of CBC and KKNI-Based Curriculum is required, learning outcomes for institution and course learning outcomes are formulated prior to devise list of courses and course distribution. Admittedly, credits of the whole program and semesterly credits distribution are successivey determined. The recent curriculum has put its quality assurance and it might be applicable to adopt.